DpiA Binding to the Replication Origin of Escherichia coli Plasmids and Chromosomes Destabilizes Plasmid Inheritance and Induces the Bacterial SOS Response - Miller, Christine (American Society for Microbiology, 2003)
The dpiA and dpiB genes of Escherichia coli, which are orthologs of genes that regulate citrate uptake and utilization in Klebsiella pneumoniae, comprise a two-component signal transduction system that can modulate the replication of and destabilize the inheritance of pSC101 and certain other plasmids. Here we show that perturbed replication and inheritance result from binding of the effector protein DpiA to A+T-rich replication origin sequences that resemble those in the K. pneumoniae promoter region targeted by the DpiA ortholog, CitB. Consistent with its ability to bind to A+T-rich origin sequences, overproduction of DpiA induced the SOS response in E. coli, suggesting that chromosomal DNA replication is affected. Bacteria that overexpressed DpiA showed an increased amount of DNA per cell and increased cell size—both also characteristic of the SOS response. Concurrent overexpression of the DNA replication initiation protein, DnaA, or the DNA helicase, DnaB—both of which act at A+T-rich replication origin sequences in the E. coli chromosome and DpiA-targeted plasmids—reversed SOS induction as well as plasmid destabilization by DpiA. Our finding that physical and functional interactions between DpiA and sites of replication initiation modulate DNA replication and plasmid inheritance suggests a mechanism by which environmental stimuli transmitted by these gene products can regulate chromosomal and plasmid dynamics.